Comprehensive review of visual defects reported with topiramate - Ford L (Dove Medical Press, 2017)
Lisa Ford,1 Jeffrey L Goldberg,2 Fred Selan,1 Howard E Greenberg,1 Yingqi Shi1 1Janssen Research & Development, LLC, Titusville, NJ, 2Byers Eye Institute, Stanford University, Palo Alto, CA, USA Objective: The objective of this study was to analyze clinical patterns of visual field defects (VFDs) reported with topiramate treatment and assess possible mechanism of action (MOA) for antiepileptic drug (AED) associated VFDs.Methods: A comprehensive topiramate database review included preclinical data, sponsor’s clinical trials database, postmarketing spontaneous reports, and medical literature. All treatment-emergent adverse events (TEAEs) suggestive of retinal dysfunction/damage were summarized. Relative risk (RR) was computed from topiramate double-blind, placebo-controlled trials (DBPCTs) data.Results: Preclinical studies and medical literature review suggested that despite sharing gamma-aminobutyric acid (GABA)-ergic MOA with other AEDs, topiramate treatment was not associated with VFDs. TEAEs suggestive of retinal dysfunction/damage were observed in 0.3%–0.7% of adults and pediatric patients with topiramate (N=4,679) versus ≤0.1% with placebo (N=1,834) in DBPCTs for approved indications (epilepsy and migraine prophylaxis); open-label trials (OLTs) and DBPCTs for investigational indications had similar incidence. Overall, 88% TEAEs were mild or moderate in severity. Serious TEAEs were very rare (DBPCTs: 0%; OLTs: ≤0.1%), and most were not treatment limiting, and resolved. The most common visual TEAEs (approved indications) were VFD, scotoma, and optic atrophy. The incidence of TEAEs in DBPCTs (approved and investigational indications) was higher in topiramate-treated (N=9,169) versus placebo-treated patients (N=5,023; 0.36% vs 0.24%), but the RR versus placebo-treated patients was not significant (RR: 1.51 [95% confidence interval: 0.78, 2.91]).Conclusion: VFDs do not appear to be a class effect for AEDs with GABA-ergic MOA. The RR for VFDs is not significantly different between topiramate and placebo treatment. Keywords: gamma-aminobutyric acid, retinal dysfunction, scotoma, topiramate, visual field defects